Debunking Morality: Lessons from the EAAN Literature. (22nd July 2016) - Moon, Andrew
Abstract: This article explores evolutionary debunking arguments as they arise in metaethics against moral realism and in philosophy of religion against naturalism. Both literatures have independently grappled with the question of which beliefs one may use to respond to a potential defeater. In this article, I show how the literature on the argument against naturalism can help clarify and bring progress to the literature on moral realism with respect to this question. Of note, it will become clear that the objection that the moral realist begs the question, when appealing to the truth of some of her moral beliefs, is unsuccessful.